Maximum likelihood Estimation for the Linear Exponential Distribution Using Grouped Data - โชติจันทึก, คณิศา (KKU Science Journal, 2014)
Using statistical distribution functions to explain data behavior is the scientific process accepted all around the world. They could show tendency and information of data used in decision making to apply in any area. Estimation of parameters for statistical distribution functions are seen as a crucial preliminary process. However, it is found that data observing in some situations could not be completely collected especially in the situation rested on linear exponential distribution because they depended on time that is very difficult to observe. A technique used to solve this problem is collecting the grouped data. This paper presents using maximum likelihood method to estimate parameters for linear exponential distribution by observing grouped data. The result from this study is a fundamental alternative technique to explain data corresponded with linear exponential distribution using grouped data.